The Relationship between Dietary Patterns, Physical Activity and Protein Intake with Dysmenorrhea in Female Students at SMPN 4 Samarinda - Kamalul Huda; Rieska Indah Mulyani; Eka Farpina; Wiryanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Dysmenorrhea is often experienced by most women during their menstrual cycle. This condition is characterized by lower abdominal pain ranging from mild to severe and accompanied by other symptoms such as nausea, vomiting, diarrhea, headaches and general discomfort. The aim of the research was to determine the relationship between diet, physical activity and protein intake with dysmenorrhea in female students at SMP Negeri 4 Samarinda. This type of research is quantitative research using a cross sectional design. The research sample was 64 class VIII students at SMPN 4 Samarinda who experienced dysmenorrhea. The research was conducted in March-April 2023. Data analysis used the chi-square test. The research results showed a relationship between physical activity level and dysmenorrhea with a p-value of 0.000 <0.05. Diet and protein intake have no relationship with dysmenorrhea because the p-value is> 0.05.